Rancang Alat Reaktor untuk Pembuatan Pabrik Cinnamaldehid (C9H8O) Menggunakan Aldol Kondensasi dengan Kapasitas Produksi 20.000 Ton/Tahun - Uswatun Khasanah; Zuhd Ma'sum; Susy Yuniningsih (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2021)
Cinnamaldehyde (C9H8O) makes perfume, aroma enhancers in making candy, soap, and medicine. Factory designed with a capacity of 20,000 Tons/Year. The factory, located in Gresik Industrial Area, East Java, operates 330 days a year with 24 hours/day production. They were making Cinnamaldehyde using the Aldol Condensation process by reacting Acetaldehyde and Benzaldehyde with a Sodium Hydroxide catalyst in the reactor at a temperature of 70oC and a pressure of 4.7 atm with a conversion of 85%. The reaction is exothermic, so to maintain the temperature of the reaction, water cooling is needed. Then Cinnamaldehyde is neutralized with H2SO4 in the neutralizer, and Cinnamyldehyde is further separated in a distillation tower. The results of the economic analysis show that the Cinnamaldehyde plant requires fixed capital (Fixed Capital Investment) of IDR 525,828,918,487 and Working Capital Investment of IDR 92,793,338,557. This factory has a Return Of Investment (ROI) before tax 64.45% and after-tax 73.24%; Payout Time 1.37 years, Shut Down Point (SDP) 61,96%, Break Event Points 44.2%, and Internal Rate Of Return (IRR ) 19.22%. Based on the economic review, it can be concluded that the Cinnamaldehyde factory is feasible to build.